2021
DOI: 10.37004/sefm/2021.22.1.004
|View full text |Cite
|
Sign up to set email alerts
|

Implementación y uso clínico de la radioterapia adaptativa. Informe del grupo de trabajo de radioterapia adaptativa de la Sociedad Española de Física Médica (SEFM)

Abstract: La radioterapia adaptativa (Adaptive Radiation Therapy, ART) se puede definir como la modificación del plan de tratamiento administrado a un paciente durante el curso de la radioterapia para tener en cuenta los cambios en la anatomía. La aplicación de ART supone un cambio en el proceso radioterápico que implica el uso de numerosos recursos adicionales, no estando implementada de forma general. Así, aun tratándose de una idea introducida hace más de 20 años, todavía a fecha de hoy son objeto de estudio mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 197 publications
(282 reference statements)
0
2
0
4
Order By: Relevance
“…A separate study found that positional deviation that remains after correcting the actual positioning to the planned position was observed to be greater than 5 mm in 10% of patients if imaging is performed daily, and in 33% of patients submitted to weekly imaging [ 8 ]. Different factors such as weight loss, disease progression, the timing of the second image, location of the primary tumor, nutritional intervention, functional impairment, immobilization-related factors, shrinkage or deformation of the treatment volume, displacement of the lymph nodes and medial parotid gland and type of treatment have all been evaluated as triggers for re-planning [ 8 , 25 , 26 ]. Other studies report more frequent changes to weight, neck, OAR, and tumor shape and position than those observed here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A separate study found that positional deviation that remains after correcting the actual positioning to the planned position was observed to be greater than 5 mm in 10% of patients if imaging is performed daily, and in 33% of patients submitted to weekly imaging [ 8 ]. Different factors such as weight loss, disease progression, the timing of the second image, location of the primary tumor, nutritional intervention, functional impairment, immobilization-related factors, shrinkage or deformation of the treatment volume, displacement of the lymph nodes and medial parotid gland and type of treatment have all been evaluated as triggers for re-planning [ 8 , 25 , 26 ]. Other studies report more frequent changes to weight, neck, OAR, and tumor shape and position than those observed here.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies report more frequent changes to weight, neck, OAR, and tumor shape and position than those observed here. The dose impact of these changes has been shown to range from insignificant to variations on the order of 2-3 Gy when compared to the plan [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…53 Asimismo, el grupo de trabajo sobre ART de la Sociedad Española de Física Médica (SEFM) ha presentado un informe describiendo los principios de esta técnica ART, así como los elementos necesarios para su implementación y la validación de los algoritmos involucrados. 54…”
Section: Automatización En El Proceso De Segmentación Y Planificaciónunclassified
“…El fabricante debe proporcionar información detallada sobre su algoritmo de registro para que el usuario pueda realizar un uso adecuado del mismo. 53,54 El proceso de registro de imágenes conlleva incertidumbres que se deben evaluar y considerar, ya que éstas pueden tener un impacto importante en el tratamiento de los pacientes. Con respecto al registro deformable, la SEFM ha publicado recientemente un informe del grupo de trabajo sobre radioterapia adaptativa donde se describe el uso de este tipo de registro y las validaciones necesarias.…”
Section: Modelado De Los Sistemas De Imagen Y Registro De Imagenunclassified
See 1 more Smart Citation